Exploring the Physiology of Silicon and Its Impact on Sugarcane Growth, Development, Yield, and Juice Quality - Costa, Milton Garcia [UNESP]; de Mello Prado, Renato [UNESP]; Teixeira, Gelza Carliane Marques [UNESP]; Oliveira, Kamilla Silva [UNESP]; Da Silva, Gilmara Pereira [UNESP]; de Souza, Jonas Pereira (My University, 2024)
The use of silicon (Si) in agriculture is a sustainable management strategy for both stressed and unstressed sugarcane. The benefits of Si are multiple, including modifying the biochemical, physiological, and nutritional processes of sugarcane plants, attributing greater tolerance to stress, and extending the longevity of the sugarcane field. These Si benefits correlate with different antioxidant defense mechanisms, from the improvement of photosynthetic machinery and photosynthetic efficiency of plants, directly impacting plant performance. In this scenario, this study will address the role of Si in the physiology and nutritional balance of plants and the impact of this beneficial element in mitigating nutritional disorders and water deficit to reduce yield losses and improve the quality of sugarcane juice.
Keywords: beneficial element; nutritional balance; plant stress; Saccharum officinarum L.; sustainable management; water deficit